The Perception of Young Women towards Beauty Value in Beauty Advertisements - Amalia, Fatya Alty; Andani, Adiva Rakhma; Guteres, Alexandre Desausa (Politeknik Negeri Bandung, 2023)
Fulfillment of beauty standards with a thin body, fair skin, and straight hair should have status as an old idea that does not need to be perpetuated. There is a change from women who no longer interpret beauty according to the standards that are instilled. This is in line with the many brands that are starting to break the stereotype of beauty when creating their campaigns and advertising media, with values that are increasingly changing, now many beauty brands have created positive and inclusive campaigns to touch more people who care about physical and non-physical beauty. The current study aims to know how female customers perceive the value of beauty toward the ideal women that are being promoted in media, especially in advertising, and how its impacts women. To explore the perceptions of women as a customer, this study uses a qualitative method to dig deeply into how the perception of the customer will work against the brands. This study suggests that brands, especially beauty brands, to put attention to female customers’ perception of how they want to appear in any media that exist. Instead of focusing on idealized women, brands should use a more natural model which might bring inclusion and diversity.